2013
DOI: 10.2147/ijn.s38011
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of a conjugated poly(lactide-ethylene glycol) nanoparticle depot formulation for prolonged insulin delivery in the diabetic rabbit model

Abstract: Poly(ethylene glycol) (PEG) and polylactic acid (PLA)-based copolymeric nanoparticles were synthesized and investigated as a carrier for prolonged delivery of insulin via the parenteral route. Insulin loading was simultaneously achieved with particle synthesis using a double emulsion solvent evaporation technique, and the effect of varied PEG chain lengths on particle size and insulin loading efficiency was determined. The synthesized copolymer and nanoparticles were analyzed by standard polymer characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In this context, a significant consideration for the clinical development of NPs is the concentration of emulsifier, which at high levels can be toxic to kidneys. In the present studies, the PLA-PEG and PLA-PEGPPG-PEG NPs were prepared using a double emulsion solvent evaporation method (44). Our results show that an advantage of using PEG-PPG-PEG as a block copolymer in preparation of PLA NPs is that emulsifier concentrations can be markedly reduced for PLA NP stabilization at pH 7.4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, a significant consideration for the clinical development of NPs is the concentration of emulsifier, which at high levels can be toxic to kidneys. In the present studies, the PLA-PEG and PLA-PEGPPG-PEG NPs were prepared using a double emulsion solvent evaporation method (44). Our results show that an advantage of using PEG-PPG-PEG as a block copolymer in preparation of PLA NPs is that emulsifier concentrations can be markedly reduced for PLA NP stabilization at pH 7.4.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work had demonstrated that increasing PEG chain length from 1 to 4 kDa significantly improves the hydrophilicity and flexibility of block copolymers (44). Consequently, we analyzed the effects of different lengths of the PEG block and found that increases in PEG chain length improves NuBCP-9 loading.…”
Section: Discussionmentioning
confidence: 99%
“…Capsules with diclofenac dissolved in an oil core were reported by Guterres et al ( 1995 ) prepared with the nanoprecipitation technique. The preparation techniques also allow the protection of large biomolecules, as plasmid DNA (Perez et al, 2001 ) and proteins (Pillay et al, 2013 ; Zaric et al, 2013 ) as well as the encapsulation of hydrophobized magnetic iron oxides in PLA based nanoparticles. Using the emulsion/solvent evaporation technique, Urban et al ( 2009 ) prepared poly-L-lactic acid (PLLA) nanoparticles of around 100 nm with almost 40 wt% of iron oxide.…”
Section: Applicationsmentioning
confidence: 99%
“…Encapsulated material can either be released by diffusion from the polymeric matrix of the nanoparticles, and seems to depend on several factors as the preparation conditions, and the solubility of the drug in the dispersion medium. The reports range from few minutes to several days (Bourges, 2003 ; Pillay et al, 2013 ). The degradation of the polymeric matrix seems to play a minor role, only, as it is quite slow at physiological pH.…”
Section: Applicationsmentioning
confidence: 99%
“… 17 Hence, HA and GCS-based composite biomaterials could be used as a newly designed nanocarrier system for SrR encapsulation. Poly(ethylene glycol) diacrylate (PEGDA) 18 is classified by the US Food and Drug Administration as a safe polymeric material for clinical use. It can further be used as an efficient hydrogel scaffold system in tissue engineering.…”
Section: Introductionmentioning
confidence: 99%